Lateral scale calibration for focus variation microscopy - Alburayt, Anas; Syam, Wahyudin P.; Leach, Richard (IOP Publishing, 2018)
Areal surface texture measuring instruments can be calibrated by determining a set of metrological characteristics currently in the final stages of standardisation. In this paper, amplification, linearity and perpendicularity characteristics have been determined to calibrate the lateral performance of a focus variation microscope. The paper presents a novel and low-cost material measure and procedures that are used to determine the characteristics. The material measure is made of stainless steel with a cross-grating grid of hemispherical grooves. The design, manufacturing and calibration of the material measure are discussed. The (20 × 20) mm grid is measured with and without image stitching. The results show that the proposed material measure and procedures can be used to determine the error of the amplification, linearity and perpendicularity characteristics. In addition, the lateral stage error can be significantly reduced by measurement with image stitching.